Case of Challenges and Solution of Coping Skill Learning in Kindergarten - Muthmainah Muthmainah; Ika Budi Maryatun; Oktaviana Maharani; Zehra Khushal (Jurnal Pendidikan Anak, 2026)
Coping skills for early childhood are children's ability to face and manage challenging or stressful situations. These skills are important because they can help children develop adaptation and problem-solving abilities, and maintain their emotional well-being. Unfortunately, not all kindergarten teachers are able to train coping effectively through classroom learning. The purpose of this study is to describe the challenges and solutions of coping learning in kindergarten. Schools that have implemented coping learning need to be studied to provide a positive impact for other institutions that have not implemented. This study used a qualitative case study methodology, which used data sources in the form of in-depth interviews and observations. The research subjects were the school principal, vice principal for curriculum, and classroom teachers. Data were analyzed qualitatively using the Miles and Huberman model. The results showed that the challenges of coping learning are the need for teacher mastery of coping learning materials, the importance of teacher creativity to design coping learning, and parental involvement. Solutions include regular teacher training, and school-based programs, and school-parent partnerships. This study provides unique insights into the challenges and solutions in developing coping skill learning in kindergarten. This research can serve as a bridge for policy makers in designing coping skill-based education programs for kindergarten students.